Experimental Analysis of NACA-0015 Airfoil Performance: CFD and Wind Tunnel Validation of Lift, Drag, and Stall Behavior - Salem Fathi Elsheltat; Haithem Elderrat; Eman Abdulsalam; Ali Alhussain Altaweel (المجلة الأفروآسيوية للبحث العلمي, 2024)
This work presents an experimental analysis of the aerodynamic performance of the NACA-0015 airfoil, focusing on the effects of varying the angle of attack on lift, drag, and stall behavior. The design and optimization of an airplane’s wing are essential for enhancing lift and minimizing drag, both of which are influenced by changes in the angle of attack during flight. Engineering these aerodynamic dynamics, experiments were conducted using a low-speed wind tunnel at the Misurata University Faculty of Engineering’s labs. This setup facilitated the measurement of lift and drag forces across various flow velocities and angles of attack, with a particular focus on identifying early stall points that occur at lower flow velocities. The experimental data were then compared with existing Computational Fluid Dynamics (CFD) simulation results to validate the accuracy and reliability of the experimental findings. This thorough approach provides a powerful insight into the flow dynamics around the NACA-0015 airfoil. This comprehensive approach offers a general understanding of the flow behavior over the NACA-0015 airfoil, expanding our knowledge of its aerodynamic performance and driving advancements in airfoil research within the aviation sector.